The Papers of Thomas A. Edison The Wizard of Menlo Park, 1878 - Edison, Thomas A. (Johns Hopkins University Press, 1998)
This newest volume in the acclaimed Papers of Thomas A. Edison covers one year in the life of America's greatest inventor-1878. That year Edison, whom a New York newspaper in the spring first called "the Wizard of Menlo Park," developed the phonograph, one of his most famous inventions; made a breakthrough in the development of telephone transmitters, which made the instrument commercially viable; and announced the advent of domestic electric lighting, with only a few weeks' worth of tinkering necessary to complete its design (the announcement sent gas-company stocks plummeting; the research and development went on for four years).These inventions brought Edison financial support for his work and attention from the public. In January investors in the Edison Speaking Phonograph Company agreed to fund development work on the phonograph. The invention made Edison internationally famous and in May he traveled to Washington, D.C., to show the phonograph at the National Academy of Sciences, to Congress, and to President Rutherford B. Hayes at the White House. That same month Western Union agreed to pay Edison an annual salary of $6,000 for his telephone inventions, although other support from the company declined following the death of its president, William Orton. The stress of unceasing public attention, including a trans-Atlantic dispute over the question of who invented the microphone, led an exhausted Edison to travel west during the summer to witness a solar eclipse but also to seek rest. His six-week trip took him to San Francisco and the Yosemite region of California. Edison began working on electric lighting after his return and in October the Edison Electric Light Company was formed to support his research.